Continental shelf and geopolitics: Chile, and Argentina in the southern seas - Jiménez Cabrera, Diego; Manzano Iturra, Karen (Estudios Avanzados, 2023)
The continental shelf is one of the future issues in the geopolitics of the oceans. Due to a growing interest in the southern seas, the continental shelf and consequently the projection towards Antarctica has also acquired an international relevance, due to the large number of interests involved in the surrounding region, as in the case of the Antarctic Peninsula, where Chile and Argentina are present. Both countries have carried out a series of cartography in the region, which responds to the need to maintain their presence on the continental shelf and therefore, of the Antarctic projection. Through this article, it is intended to analyze the situation of the continental shelf, through geopolitics in the area of the southern seas, through a qualitative methodology with work from sources, which seek to understand the current situation and its implications in the relationship of both states. La plataforma continental es uno de los temas de futuro en la geopolítica de los océanos. Debido a un creciente interés en los mares australes, la plataforma continental y por consiguiente la proyección hacia la Antártica también ha adquirido una relevancia internacional, debido a la gran cantidad de intereses involucrados en la región circundante, como en el caso de la península Antártica, donde Chile y Argentina están presentes. Ambos países han realizado una serie de mapas de la región, que responden a la necesidad de mantener su presencia en la plataforma continental y por consiguiente, de la proyección antártica. A través del presente artículo, se analiza la situación de la plataforma continental, por medio de la geopolítica en la zona de los mares australes, mediante una metodología cualitativa con trabajo de fuentes primarias y secundarias, que buscan comprender la situación actual y sus implicancias en la relación de ambos Estados.